Effect of Drying-Wetting Cycles on Engineering Properties of Expansive Soils Modified by Industrial Wastes - Chengfu Chu; Meihuang Zhan; Qi Feng; Dong Li; Long Xu; Fusheng Zha; Yongfeng Deng (Advances in Materials Science and Engineering)
The swelling properties of expansive soils can be reduced by the addition of modifiers. Nevertheless, the performance deterioration after modification occurs when weathering for a long term. Therefore, in this study, the effect of drying-wetting cycles on swelling behaviour and compressibility of modified expansive soils with the iron tailing sand and calcium carbide slag has been investigated. The swelling potential initially increases and subsequently decreases with the increasing number of cycles, reaches the peak at the seventh cycle, and tends to equilibrium after the tenth cycle. These results show that drying-wetting cycles will destroy the soil structure. The compressibility of modified expansive soils increases with the drying-wetting cycles, where an empirical formula between compressibility and the cycle number was established. Microstructural analysis is performed using mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM). The results of microstructural analysis show a tendency of degradation process.